(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This review sought to show the main ideas of Uno’s study of Artaud’s poetics. It was observed that Uno forms an intense dialogue with concepts of philosophy, such as the body without organs and continuous variation, present especially in the work of Deleuze and Guattari. The aim was to show the current nature of Artaud’s thought, his vision of body politics, and its echoes in the artistic and philosophical scene.